Underwater non-dispersible grouting material as well as preparation method and application thereof
By mixing red mud with other components in a specific proportion, an underwater non-dispersed grouting material with excellent fluidity and curing properties is prepared, which solves the problem of long dilution and curing time of traditional grouting materials underwater, and achieves efficient underwater construction and resource recycling.
Patent Information
- Application Number
- CN202411928543.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-25
- Publication Date
- 2025-03-18
AI Technical Summary
Traditional cement-based grouting materials are easily diluted and dispersed under water, resulting in slurry loss, unable to effectively fill gaps, and have a long curing time, affecting construction efficiency.
The underwater non-dispersible grouting material with red mud as the basic raw material is used, and grouting materials with excellent fluidity, non-dispersibility and curing properties are prepared by mixing red mud, alkali trigger, silicate cement, anti-dispersant and water reducing agent in a specific proportion.
It has achieved good construction fluidity and compressive strength in the underwater environment, shortened the settling time, improved durability and corrosion resistance, and used industrial solid waste red mud to achieve the recycling of resources.
Smart Images

Figure BDA0005209773720000171
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of construction engineering, and in particular to an underwater non-dispersible grouting material and a preparation method and application thereof. Background Art
[0002] Grouting materials are materials that can solidify under certain conditions to form solid substances and have certain mechanical strength. They are widely used in many fields such as civil engineering, environmental engineering, and mining engineering. Grouting materials cover many practical applications such as surrounding rock reinforcement and crack repair engineering in tunnel construction, pile foundation pouring crack repair engineering in bridge construction, dam and reservoir construction, and goaf management in mining engineering. At present, common grouting materials are usually cement-based slurries or chemical slurries; cement-based slurries mainly include single-liquid cement slurries, clay cement slurries, cement-water glass slurries, etc., while chemical slurries include acrylamide and polyurethane, etc., which are relatively expensive and often have toxic and environmental pollution problems, so they are generally used to treat small cracks and fine sand layers. The grouting materials used in the construction engineering field today are generally the former, but with the implementation of the carbon peak and carbon neutrality policies, the construction industry is also constantly looking for low-carbon, environmentally friendly and green raw materials to replace high-energy-consuming raw materials.
[0003] Due to the complexity and diversity of the construction environment, most grouting projects need to be constructed in a water environment. However, traditional cement-based grouting materials are easily diluted and dispersed underwater, resulting in slurry loss and inability to effectively fill gaps. In addition, cement-based grouting materials take a long time to solidify underwater, affecting construction efficiency. Therefore, it is necessary to use grouting materials that are specially designed for underwater construction and do not disperse underwater for underwater operations; they are mainly used for underwater structure reinforcement, anti-seepage, and plugging projects. Such materials can maintain good fluidity, non-dispersion, and solidification properties in underwater environments, thereby ensuring construction quality and engineering effects.
[0004] Red mud is a waste material in the industrial production of alumina. Every ton of alumina produced will produce about 1.2 tons of red mud; its main components include silicon dioxide, aluminum oxide, iron oxide, silicon dioxide, and a small amount of calcium oxide, titanium oxide and other trace components. Although the main components in red mud (such as Fe2O3, Al2O3, SiO2) also have certain reactivity, the properties and quantity of their hydration reaction products are far inferior to cement, and they cannot provide sufficient strength and stability, making it difficult to use them as a resource raw material for the preparation of underwater grouting materials.
[0005] In view of this, the present invention is proposed. Summary of the invention
[0006] The first purpose of the present invention is to provide an underwater non-dispersible grouting material, which, on the one hand, is used to solve the defects that conventional grouting materials cannot maintain good construction fluidity, non-dispersibility and curing performance in underwater environments, and on the other hand, it also provides a new resource treatment method for industrial waste red mud.
[0007] The second purpose of the present invention is to provide a method for preparing the underwater non-dispersible grouting material, which is simple, easy to operate, low-cost, environmentally friendly and has good scalability.
[0008] The third object of the present invention is to provide the use of the underwater non-dispersible grouting material in the field of construction engineering.
[0009] In order to achieve the above-mentioned purpose of the present invention, the following technical solutions are particularly adopted:
[0010] An underwater non-dispersible grouting material comprises the following components by mass:
[0011] 150-250 parts of red mud, 10-80 parts of Portland cement, 1-8 parts of alkali activator, 3.5-10 parts of anti-dispersant, 0.5-8 parts of water reducer and some water;
[0012] The alkaline activator comprises the following components: biomass ash, tungstate, silicate, microsilica powder, arginine and inorganic base.
[0013] A method for preparing the underwater non-dispersible grouting material comprises the following steps:
[0014] The biomass ash, tungstate, silicate, microsilica powder, arginine and inorganic base are fully mixed to obtain an alkali activator;
[0015] The red mud, the alkali activator and water are fully mixed, and then allowed to stand to obtain a mixture;
[0016] The mixed material, silicate cement, anti-dispersant and water reducing agent are fully mixed to obtain the underwater non-dispersible grouting material.
[0017] And the use of the underwater non-dispersible grouting material in the field of construction engineering.
[0018] Compared with the prior art, the present invention has the following beneficial effects:
[0019] (1) The present invention proposes an underwater non-dispersible grouting material obtained by resource utilization of red mud as a basic raw material, which has excellent flow state, setting time, compressive strength, good underwater anti-dispersion performance, construction fluidity and durability; at the same time, industrial solid waste red mud is used as the main raw material to partially replace the cement used in conventional grouting materials, saving land resources required for red mud accumulation, reducing environmental pressure, realizing the recycling of resources, and complying with the concept of sustainable development.
[0020] (2) The present invention dissolves silicates and aluminates in red mud under the action of an alkaline activator of a specific component, and then the oligomers in the dissolved product condense to form a polymer product with a longer chain or three-dimensional network structure; the polymer product is mainly high-strength and high-density hydrated calcium aluminosilicate and hydrated calcium silicate, and over time, the three-dimensional network structure gradually becomes denser and stronger. In comparison, the hydration product of cement-based materials not only forms high-strength hydrated calcium silicate, but also forms a large amount of low-strength and low-density calcium hydroxide; therefore, under the same preparation method and curing age conditions, the mechanical properties of the red mud-based grouting material used in the present invention are significantly better than those of pure cement-based grouting materials, and have better physical and mechanical properties, durability and corrosion resistance.
[0021] (3) The present invention introduces an alkali activator of a specific component, which, in addition to conventional sodium hydroxide and sodium silicate, also contains biomass ash (such as corn cob ash and corn stalk ash, olive biomass ash, etc.), whose high pH value (13-14) and high potassium content make it a substitute for alkali metal hydroxides; in addition, the biomass ash used in the present invention contains an amorphous silica component, which has a high reactivity and can react with calcium hydroxide during the cement hydration process to form more calcium silicate hydrate (CSH) gel, thereby improving the strength and durability of the grouting material, so as to improve the crack resistance and impermeability.
[0022] (4) The present invention also introduces an anti-dispersion agent of a specific component, which uses polyvinyl alcohol modified with sodium alginate as one of the main components. The modified polyvinyl alcohol can form a three-dimensional network structure in the red mud slurry, further enhancing the stability of the slurry, so that the grouting material prepared by the present invention has excellent underwater anti-dispersion performance. At the same time, polyvinyl alcohol can form a layer of water film on the surface of red mud particles, reduce the evaporation of water, maintain the humidity inside the grouting material, reduce the self-shrinkage and drying shrinkage of red mud, and increase the fluidity and pumpability of the grouting material slurry. Furthermore, polyvinyl alcohol can be used as an alkali-panning inhibitor, which can effectively prevent alkali-panning after the grouting material hardens and avoid pollution to the water body. DETAILED DESCRIPTION
[0023] The technical scheme of the present invention will be clearly and completely described below in conjunction with specific embodiments, but those skilled in the art will appreciate that the following described embodiments are part of embodiments of the present invention, rather than all embodiments, and are only used to illustrate the present invention, and should not be considered as limiting the scope of the present invention. Based on the embodiments in the present invention, all other embodiments obtained by those of ordinary skill in the art without making creative work are within the scope of protection of the present invention. Those who do not specify specific conditions in the embodiments are carried out according to conventional conditions or conditions recommended by the manufacturer. Those who do not specify the manufacturer for reagents or instruments used are conventional products that can be purchased commercially. In addition, the terms "first", "second" and "third" are only used for descriptive purposes and cannot be interpreted as indicating or implying relative importance.
[0024] The first aspect of the present invention is to provide an underwater non-dispersible grouting material, which mainly includes the following components by mass: 150 to 250 parts of red mud, 10 to 80 parts of silicate cement, 1 to 8 parts of alkali activator, 3.5 to 10 parts of anti-dispersant, 0.5 to 8 parts of water reducer and some water.
[0025] As an optional embodiment, the mass fractions of each essential component of the underwater non-dispersible grouting material include but are not limited to: red mud 150, 160, 170, 180, 190, 200, 210, 220, 230, 240, 250; Portland cement 10, 20, 30, 40, 50, 60, 70, 80; alkali activator 1, 2, 3, 4, 5, 6, 7, 8; anti-dispersant 3.5, 4, 5, 6, 7, 8, 9, 9.5, 10; water reducer 0.5, 1, 2, 3, 4, 5, 6, 7, 7.5, 8; the above mass fractions are all dimensionless, and the corresponding mass fractions can use any one of the point values listed above, or the numerical range formed by any two point values.
[0026] As an optional implementation manner, the amount of water used is 100 to 250 parts by mass.
[0027] As a preferred embodiment, the silicate cement is ordinary silicate cement with the industry code PO; it is made by grinding silicate cement clinker, 6% to 15% or 5% to 20% of mixed materials and an appropriate amount of gypsum; in the present invention, ordinary silicate cement with a strength grade of 42.5 or 42.5R is preferably used.
[0028] As a preferred embodiment, the water reducer is a polycarboxylate water reducer; those skilled in the art can obtain any polycarboxylate water reducer through commercial channels for use.
[0029] As a preferred embodiment, the underwater non-dispersible grouting material further comprises: 0.1 to 50 parts by mass of fly ash or 0.1 to 50 parts by mass of sulphoaluminate cement or both.
[0030] It is worth noting that, in the following preferred embodiments, the base activator and the anti-dispersion agent in the present invention are composed of specific components.
[0031] (a) The alkaline activator comprises the following components: biomass ash, tungstate, silicate, microsilica powder, arginine and inorganic base.
[0032] As a preferred embodiment, the biomass ash includes one or a combination of two or more of corn cob ash, corn stalk ash or olive biomass ash.
[0033] As a preferred embodiment, the fineness modulus of the biomass ash is 200 mesh to 400 mesh.
[0034] As a preferred embodiment, the tungstate includes at least one of sodium tungstate and potassium tungstate, and the silicate includes at least one of sodium silicate and potassium silicate. As a more preferred embodiment, the tungstate is sodium tungstate, and the silicate is sodium silicate.
[0035] As a preferred embodiment, the particle size of the microsilica powder is 0.5 μm to 1.25 μm.
[0036] As a preferred embodiment, the inorganic base includes at least one of sodium hydroxide, potassium hydroxide and calcium hydroxide. As a more preferred embodiment, the inorganic base is sodium hydroxide.
[0037] As a preferred embodiment, the weight ratio of the components of the alkaline activator, measured in parts by mass, includes: 30-80 parts of biomass ash, 8-20 parts of tungstate, 15-30 parts of silicate, 5-10 parts of microsilica, 0.5-6 parts of arginine and 2-10 parts of inorganic base.
[0038] As an optional embodiment, the mass fractions of each essential component of the alkaline activator include but are not limited to: biomass ash 30, 35, 40, 50, 60, 70, 75, 80; tungstate 8, 9, 10, 12, 14, 15, 16, 18, 20; silicate 15, 16, 18, 20, 22, 25, 26, 28, 30; microsilica 5, 6, 7, 8, 9, 10; arginine 0.5, 1, 1.5, 2, 2.5, 3, 4, 5, 5.5, 6; inorganic base 2, 3, 4, 5, 6, 7, 8, 9, 10; the above mass fractions are dimensionless, and the weight fraction of the alkali activator is not measured in proportion to the weight fraction of the underwater non-dispersible grouting material, and the corresponding mass fraction can adopt any one of the point values listed above, or can adopt the numerical range formed by any two point values.
[0039] (b) The anti-dispersion agent includes polyvinyl alcohol modified with sodium alginate, cellulose compounds, stone powder and maltodextrin.
[0040] As a preferred embodiment, the sodium alginate-modified polyvinyl alcohol is prepared by the following method: separately preparing an aqueous solution of sodium alginate and an aqueous solution of polyvinyl alcohol, then mixing the two, and adding an aqueous solution of a cross-linking agent thereto and reacting; after the reaction is completed, freeze-drying is performed to obtain the sodium alginate-modified polyvinyl alcohol.
[0041] As a more preferred embodiment, the cross-linking agent includes at least one of calcium chloride, calcium sulfate, glutaraldehyde, and N,N'-methylenebisacrylamide.
[0042] As a more preferred embodiment, the molecular weight of the polyvinyl alcohol is 30,000 to 50,000.
[0043] As a more preferred embodiment, during the configuration of the aqueous solution of sodium alginate and the aqueous solution of polyvinyl alcohol, one or more of the following methods are used to assist the preparation, such as oscillation, stirring, shaking, centrifugation, ultrasound, and heat treatment, so as to obtain a uniformly dispersed aqueous solution. It is further preferred to use a combination of stirring and heat treatment, the temperature of the heat treatment is 40°C to 70°C, the stirring frequency is 50rpm to 500rpm, and the treatment time is subject to the dispersion of the system, which is not strictly limited in the present invention.
[0044] As a more preferred embodiment, the mass ratio of sodium alginate to water in the aqueous solution of sodium alginate is (0.9-3): (100-350), the mass ratio of polyethylene to water in the aqueous solution of polyvinyl alcohol is (0.3-1.2): (50-200), and the mass ratio of the crosslinking agent to water in the aqueous solution of the crosslinking agent is (1-5): (80-120).
[0045] As a more preferred embodiment, the mass ratio of the sodium alginate, the polyvinyl alcohol and the cross-linking agent is (0.9-3): (0.3-1.2): (1-5).
[0046] As a more preferred embodiment, the dropping time is 15 min to 40 min, and the dropping is performed under stirring.
[0047] As a more preferred embodiment, after the dropwise addition, the reaction time is 20 min to 50 min.
[0048] As a more preferred embodiment, the freeze-drying temperature is -20°C to -10°C, and the freeze-drying time is 20 hours to 28 hours. As a further preferred embodiment, the freeze-drying temperature is -15°C, and the freeze-drying time is 24 hours.
[0049] As a more preferred embodiment, after the freeze-drying, the method further comprises: grinding the sodium alginate-modified polyvinyl alcohol to a particle size of 200-300 meshes.
[0050] As a preferred embodiment, the cellulose compound includes at least one of hydroxymethyl cellulose, hydroxyethyl cellulose or hydroxypropyl methyl cellulose.
[0051] As a preferred embodiment, the stone powder includes at least one of marble powder, quartz powder or granite powder.
[0052] As a preferred implementation, the fineness of the stone powder is 200-300 mesh.
[0053] As a preferred embodiment, the weight ratio of the components of the anti-dispersant includes, by mass, 35-70 parts of polyvinyl alcohol modified with sodium alginate, 5-15 parts of cellulose compounds, 5-20 parts of stone powder and 4-8 parts of maltodextrin.
[0054] As an optional embodiment, the mass fractions of each essential component of the anti-dispersant include but are not limited to: 35, 40, 45, 50, 60, 65, 70 of polyvinyl alcohol modified with sodium alginate; 5, 6, 8, 10, 12, 14, 15 of cellulose compounds; 5, 6, 8, 10, 12, 14, 15, 16, 18, 20 of stone powder; 4, 5, 6, 7, 8 of maltodextrin; the above mass fractions are dimensionless, and the weight fractions of the anti-dispersant are not measured in proportion to the weight fractions of the underwater non-dispersible grouting material, and the corresponding mass fractions can use any one of the point values listed above, or can use the numerical range formed by any two point values.
[0055] The second aspect of the present invention is to provide a method for preparing the underwater non-dispersible grouting material as described in the first aspect, which mainly includes the following steps: first, biomass ash, tungstate, silicate, microsilica, arginine and inorganic base are fully mixed to obtain an alkali activator; then red mud, the alkali activator and water are fully mixed, and then allowed to stand to obtain a mixture; then the mixture, silicate cement, anti-dispersant and water reducer are fully mixed to obtain the underwater non-dispersible grouting material.
[0056] As a preferred implementation, the standing time is 20 min to 40 min.
[0057] As a preferred embodiment, when the raw materials of the underwater non-dispersible grouting material also include fly ash and / or sulphoaluminate cement, the preparation method includes the following steps: first, fully mix red mud, alkali activator and water, and then let it stand to obtain a mixture; then, fully mix the mixture, silicate cement, anti-dispersant, water reducer, and one or two of fly ash or sulphoaluminate cement to obtain the underwater non-dispersible grouting material.
[0058] The third aspect of the present invention is to provide a use of the underwater non-dispersible grouting material as described in the first aspect in the field of construction engineering; it can be understood that the use includes but is not limited to building materials made based on the underwater non-dispersible grouting material, buildings constructed based on the underwater non-dispersible grouting material, underwater construction methods based on the underwater non-dispersible grouting material, etc. When any product or method in the field of construction engineering involves the underwater non-dispersible grouting material, it can be used as an embodiment of the present invention.
[0059] The sodium alginate used in the embodiments of the present invention was purchased from McLean Reagent, item number S875036, which is ultra-high viscosity type I with a 1% viscosity of 500 mPa·S; the ordinary Portland cement used in the embodiments of the present invention was purchased from Conch Cement, PO42.5; the water reducer used in the embodiments of the present invention is the DS-J1 standard polycarboxylate water reducer of Guizhou Shiboshi Technology Co., Ltd.; the sulphoaluminate cement used in the embodiments of the present invention was purchased from Conch Cement; the red mud used in the embodiments of the present invention comes from Guizhou Guangl Aluminum Co., Ltd.
[0060] Example 1
[0061] An underwater non-dispersible grouting material prepared using industrial solid waste is prepared from 150 parts by mass of red mud, 2.5 parts of an alkali activator, 160 parts of water, 55 parts of ordinary Portland cement, 25 parts of fly ash, 36 parts of sulphoaluminate cement, 8.5 parts of an anti-dispersant, and 1 part of a water reducer.
[0062] A method for preparing underwater non-dispersible grouting material using industrial solid waste comprises the following steps:
[0063] S1. Preparation of alkaline activator
[0064] Take 40 parts of biomass ash (corn cob ash), 16 parts of sodium tungstate, 25 parts of sodium silicate, 8 parts of microsilica powder, 3.2 parts of arginine and 8 parts of sodium hydroxide and mix them thoroughly to obtain an alkaline activator.
[0065] S2. Preparation of anti-dispersant
[0066] Take 1.2 parts of sodium alginate and 240 parts of water in a beaker, stir for 20 minutes at 60°C to fully dissolve it to obtain solution A, take 1.5 parts of polyvinyl alcohol and add it to 90 parts of hot water at 60°C, stir for 10 minutes to fully dissolve it to obtain solution B, mix liquid A and liquid B together, start stirring, take 3.3 parts of cross-linking agent (calcium chloride) and dissolve it in 100 parts of water as liquid C for dripping, drip solution C into the AB mixture at a uniform rate for 20 minutes and continue to stir and react for 30 minutes. After the reaction is completed, place the reactant in a freeze dryer, freeze-dry at -15°C for 24 hours, take out the sample, grind it into powder and use it as sodium alginate modified polyvinyl alcohol powder. Weigh 35 parts of the above sodium alginate modified polyvinyl alcohol powder and mix it with 10 parts of hydroxypropyl methylcellulose, 25 parts of stone powder and 6 parts of maltodextrin to obtain an anti-dispersant.
[0067] S3. Preparation of underwater non-dispersible grouting material
[0068] Take 150 parts of red mud and 2.5 parts of alkali activator and add them to 160 parts of water. Stir well to evenly disperse the red mud in the water. After standing for 30 minutes, add 55 parts of ordinary Portland cement, 25 parts of fly ash, 36 parts of sulfoaluminate cement, 8.5 parts of anti-dispersant, and 1 part of water reducer. Use a cement slurry mixer to stir at low speed for 5 minutes to obtain red mud-based underwater non-dispersible grouting material.
[0069] Example 2
[0070] An underwater non-dispersible grouting material prepared using industrial solid waste is prepared from 200 parts by mass of red mud, 4.5 parts of an alkali activator, 180 parts of water, 80 parts of ordinary Portland cement, 20 parts of sulphoaluminate cement, 5.5 parts of an anti-dispersant, and 2.2 parts of a water reducer.
[0071] A method for preparing underwater non-dispersible grouting material using industrial solid waste comprises the following steps:
[0072] S1. Preparation of alkaline activator
[0073] Take 30 parts of biomass ash (corn cob ash), 10 parts of sodium tungstate, 18 parts of sodium silicate, 8 parts of microsilica powder, 2 parts of arginine and 7.8 parts of sodium hydroxide and mix them thoroughly to obtain an alkaline activator.
[0074] S2. Preparation of anti-dispersant
[0075] Take 1 part of sodium alginate and 220 parts of water in a beaker, stir for 10 minutes at 60°C to fully dissolve it to obtain solution A, take 2 parts of polyvinyl alcohol and add them to 90 parts of hot water at 60°C, stir for 15 minutes to fully dissolve it to obtain solution B, mix liquid A and liquid B together, start stirring, take 1.6 parts of cross-linking agent (calcium sulfate) and dissolve it in 100 parts of water as liquid C for dripping, drip solution C into the AB mixture at a uniform rate for 20 minutes and continue to stir and react for 30 minutes. After the reaction is completed, place the reactant in a freeze dryer, freeze-dry at -15°C for 24 hours, take out the sample, grind it into powder and use it as sodium alginate modified polyvinyl alcohol powder. Weigh 60 parts of the above sodium alginate modified polyvinyl alcohol powder and mix it with 8.6 parts of hydroxypropyl methylcellulose, 12.3 parts of stone powder and 6.6 parts of maltodextrin to obtain an anti-dispersant.
[0076] S3. Preparation of underwater non-dispersible grouting material
[0077] Take 200 parts of red mud and 4.5 parts of alkali activator and add them to 180 parts of water. Stir thoroughly to evenly disperse the red mud in the water. After standing for 30 minutes, add 30 parts of ordinary Portland cement, 20 parts of sulfoaluminate cement, 5.5 parts of anti-dispersant, and 2.2 parts of water reducer. Use a cement slurry mixer to stir at low speed for 5 minutes to obtain red mud-based underwater non-dispersible grouting material.
[0078] Example 3
[0079] An underwater non-dispersible grouting material prepared using industrial solid waste is prepared from 220 parts by mass of red mud, 4.7 parts of an alkali activator, 165 parts of water, 20 parts of ordinary Portland cement, 50 parts of fly ash, 10 parts of sulphoaluminate cement, 7.5 parts of an anti-dispersant, and 3.7 parts of a water reducer.
[0080] A method for preparing underwater non-dispersible grouting material using industrial solid waste comprises the following steps:
[0081] S1. Preparation of alkaline activator
[0082] Take 60 parts of biomass ash (corn straw ash), 12.5 parts of sodium tungstate, 15 parts of sodium silicate, 5 parts of microsilica, 4.8 parts of arginine and 3 parts of sodium hydroxide and mix them thoroughly to obtain an alkaline activator.
[0083] S2. Preparation of anti-dispersant
[0084] Take 1.3 parts of sodium alginate and 300 parts of water in a beaker, stir for 20 minutes at 600°C to fully dissolve it to obtain solution A, take 0.5 parts of polyvinyl alcohol and add it to 100 parts of hot water at 60°C, stir for 20 minutes to fully dissolve it to obtain solution B, mix liquid A and liquid B together, start stirring, take 2.8 parts of cross-linking agent (glutaraldehyde) and dissolve it in 100 parts of water as liquid C for dripping, drip solution C into the AB mixture at a uniform rate for 20 minutes and continue to stir and react for 30 minutes. After the reaction is completed, place the reactant in a freeze dryer, freeze-dry at -15°C for 24 hours, take out the sample, grind it into powder and use it as sodium alginate modified polyvinyl alcohol powder. Weigh 50 parts of the above sodium alginate modified polyvinyl alcohol powder and mix it with 12.5 parts of hydroxypropyl methylcellulose, 18 parts of stone powder and 3.6 parts of maltodextrin to obtain an anti-dispersant.
[0085] S3. Preparation of underwater non-dispersible grouting material
[0086] Take 220 parts of red mud and 4.7 parts of alkali activator and add them to 165 parts of water. Stir well to evenly disperse the red mud in the water. After standing for 30 minutes, add 20 parts of ordinary Portland cement, 50 parts of fly ash, 10 parts of sulphoaluminate cement, 7.5 parts of anti-dispersant, and 3.7 parts of water reducer. Use a cement slurry mixer to stir at low speed for 5 minutes to obtain red mud-based underwater non-dispersible grouting material.
[0087] Example 4
[0088] An underwater non-dispersible grouting material prepared using industrial solid waste is prepared from 250 parts by mass of red mud, 5.6 parts of an alkali activator, 131 parts of water, 20 parts of ordinary Portland cement, 20 parts of fly ash, 5.8 parts of an anti-dispersant, and 5.5 parts of a water reducer.
[0089] A method for preparing underwater non-dispersible grouting material using industrial solid waste comprises the following steps:
[0090] S1. Preparation of alkaline activator
[0091] Take 80 parts of biomass ash (corn straw ash), 8 parts of sodium tungstate, 16 parts of sodium silicate, 5 parts of microsilica, 1.5 parts of arginine and 2 parts of sodium hydroxide and mix them thoroughly to obtain an alkaline activator.
[0092] S2. Preparation of anti-dispersant
[0093] Take 0.9 parts of sodium alginate and 120 parts of water in a beaker, stir for 15 minutes at 60°C to fully dissolve it to obtain solution A, take 1 part of polyvinyl alcohol and add it to 100 parts of hot water at 60°C, stir for 5-20 minutes to fully dissolve it to obtain solution B, mix liquid A and liquid B together, start stirring, take 1.3 parts of cross-linking agent (glutaraldehyde) and dissolve it in 100 parts of water as liquid C for dripping, drip solution C into the AB mixture at a uniform rate for 20 minutes and continue to stir and react for 30 minutes. After the reaction is completed, place the reactant in a freeze dryer, freeze-dry at -15°C for 24 hours, take out the sample, grind it into powder and use it as sodium alginate modified polyvinyl alcohol powder. Weigh 70 parts of the above sodium alginate modified polyvinyl alcohol powder and mix it with 12 parts of hydroxymethyl cellulose, 5 parts of stone powder and 4 parts of maltodextrin to obtain an anti-dispersant.
[0094] S3. Preparation of underwater non-dispersible grouting material
[0095] Take 250 parts of red mud and 5.6 parts of alkali activator and add them to 131 parts of water. Stir thoroughly to evenly disperse the red mud in the water. After standing for 30 minutes, add 20 parts of ordinary Portland cement, 20 parts of fly ash, 5.8 parts of anti-dispersant, and 5.5 parts of water reducer. Use a cement slurry mixer to stir at low speed for 5 minutes to obtain a red mud-based underwater non-dispersible grouting material.
[0096] Example 5
[0097] An underwater non-dispersible grouting material prepared using industrial solid waste is prepared from 250 parts by mass of red mud, 5.6 parts of an alkali activator, 126 parts of water, 15 parts of ordinary Portland cement, 10 parts of fly ash, 35 parts of sulphoaluminate cement, 3.5 parts of an anti-dispersant, and 6 parts of a water reducer.
[0098] A method for preparing underwater non-dispersible grouting material using industrial solid waste comprises the following steps:
[0099] S1. Preparation of alkaline activator
[0100] Take 68 parts of biomass ash (olive biomass ash), 14 parts of sodium tungstate, 25 parts of sodium silicate, 7.2 parts of microsilica powder, 6.6 parts of arginine and 2.5 parts of sodium hydroxide and mix them thoroughly to obtain an alkaline activator.
[0101] S2. Preparation of anti-dispersant
[0102] Take 1.1 parts of sodium alginate and 250 parts of water in a beaker, stir for 20 minutes at 60°C to fully dissolve it to obtain solution A, take 1.2 parts of polyvinyl alcohol and add it to 100 parts of hot water at 60°C, stir for 20 minutes to fully dissolve it to obtain solution B, mix liquid A and liquid B together, start stirring, take 3.8 parts of cross-linking agent (N, N'-methylenebisacrylamide) and dissolve it in 100 parts of water as drop C liquid for standby, add solution C to the AB mixture at a uniform rate for 20 minutes and continue stirring and reacting for 30 minutes. After the reaction is completed, place the reactant in a freeze dryer, freeze-dry at -15°C for 24 hours, take out the sample, grind it into powder and use it as sodium alginate modified polyvinyl alcohol powder. Weigh 40 parts of the above sodium alginate modified polyvinyl alcohol powder and mix it with 12.7 parts of hydroxyethyl cellulose, 5 parts of stone powder and 4.8 parts of maltodextrin to obtain an anti-dispersant.
[0103] S3. Preparation of underwater non-dispersible grouting material
[0104] Take 250 parts of red mud and 5.6 parts of alkali activator and add them to 126 parts of water. Stir well to evenly disperse the red mud in the water. After standing for 30 minutes, add 15 parts of ordinary Portland cement, 10 parts of fly ash, 35 parts of sulfoaluminate cement, 3.5 parts of anti-dispersant, and 6 parts of water reducer. Stir well to obtain red mud-based underwater non-dispersible grouting material.
[0105] Comparative Example 1
[0106] This comparative example uses an equal amount of ordinary Portland cement to replace the red mud in Example 1, and the specific operation steps are as follows:
[0107] Take 205 parts of ordinary Portland cement, 160 parts of water, 25 parts of fly ash, 36 parts of sulphoaluminate cement, 8.5 parts of anti-dispersant, and 1 part of water reducer, use a cement slurry mixer to stir at low speed for 5 minutes, and you can get a cement-based underwater non-dispersible grouting material.
[0108] Comparative Example 2
[0109] This comparative example uses an equal amount of ordinary Portland cement to replace the red mud in Example 2, and the specific operation steps are as follows:
[0110] Take 230 parts of ordinary Portland cement and 180 parts of water, add 30 parts of ordinary Portland cement, 20 parts of sulphoaluminate cement, 5.5 parts of anti-dispersant, and 2.2 parts of water reducer, use a cement slurry mixer to stir at low speed for 5 minutes to obtain a cement-based underwater non-dispersible grouting material.
[0111] Comparative Example 3
[0112] This comparative example uses an equal amount of ordinary Portland cement to replace the red mud in Example 3, and the specific operation steps are as follows:
[0113] Take 240 parts of ordinary Portland cement, 165 parts of water, 50 parts of fly ash, 10 parts of sulphoaluminate cement, 7.5 parts of anti-dispersant, and 3.7 parts of water reducer, use a cement slurry mixer to stir at low speed for 5 minutes, and you can get a cement-based underwater non-dispersible grouting material.
[0114] Comparative Example 4
[0115] This comparative example uses an equal amount of ordinary Portland cement to replace the red mud in Example 4, and the specific operation steps are as follows:
[0116] Take 270 parts of ordinary Portland cement, 131 parts of water, 20 parts of fly ash, 5.8 parts of anti-dispersant, and 5.5 parts of water reducer, use a cement slurry mixer to stir at low speed for 5 minutes, and obtain a cement-based underwater non-dispersible grouting material.
[0117] Comparative Example 5
[0118] This comparative example uses an equal amount of ordinary Portland cement to replace the red mud in Example 5, and the specific operation steps are as follows:
[0119] Take 265 parts of ordinary Portland cement, 126 parts of water, 10 parts of fly ash, 35 parts of sulphoaluminate cement, 3.5 parts of anti-dispersant, and 6 parts of water reducer, use a cement slurry mixer to stir at low speed for 5 minutes, and you can get a cement-based underwater non-dispersible grouting material.
[0120] Comparative Example 6
[0121] This comparative example uses other proportions in Example 1, but does not add an alkali activator to prepare an underwater non-dispersible grouting material. The specific operating steps are:
[0122] Take 150 parts of red mud, add it to 160 parts of water, stir it thoroughly to make the red mud evenly dispersed in the water, let it stand for 30 minutes, then add 55 parts of ordinary Portland cement, 25 parts of fly ash, 36 parts of sulphoaluminate cement, 8.5 parts of the anti-dispersant prepared in Example 1, and 1 part of water reducer, use a cement slurry mixer to stir at low speed for 5 minutes to obtain a red mud-based underwater non-dispersible grouting material.
[0123] Comparative Example 7
[0124] This comparative example uses a commercially available anti-dispersant to replace the anti-dispersant in Example 1. The manufacturer is Chengdu Hankang Building Materials Co., Ltd. The product name is underwater anti-dispersant additive, referred to as HK-1 anti-dispersant. The specific operation steps are:
[0125] Take 150 parts of red mud and 2.5 parts of alkali activator and add them to 160 parts of water. Stir well to make the red mud evenly dispersed in the water. After standing for 30 minutes, add 55 parts of ordinary Portland cement, 25 parts of fly ash, 36 parts of sulphoaluminate cement, 8.5 parts of HK-1 anti-dispersant, and 1 part of water reducer. Use a cement slurry mixer to stir at low speed for 5 minutes to obtain red mud-based underwater non-dispersible grouting material.
[0126] The grouting materials in the above-mentioned embodiments and comparative examples were tested, and their expansion, underwater setting time, underwater compressive strength and water entry status were tested respectively. Among them, the expansion test of the grouting material is carried out according to the national standard GB / T 2419-2005 "Method for Determining the Fluidity of Cement Mortar", by injecting the stirred grouting into a truncated cone circular mold, lifting the truncated cone circular mold, and measuring the maximum diameter of the grouting material flowing freely on the glass plane after lifting the truncated cone circular mold for 30 seconds, and the result is the expansion. The determination of the setting time is determined according to the method in the national standard GB / T 1346-2011 "Test Method for Water Consumption, Setting Time and Stability of Cement Standard Consistency".
[0127] The compressive strength is tested by the following method: a 70.7mm×70.7mm×70.7mm mold should be used for the molding of grouting slurry test blocks. The grouting material is injected into the mold. After waiting for 30 minutes, the mold containing the grouting material is placed in 20℃ water conditions for curing. After curing for 3 days, the test block after the grouting material has solidified and hardened is taken out of the mold and continued to be placed in water for curing. After the cured test block reaches a certain age, it is taken out and the compressive strength test is carried out on a pressure testing machine and the value is recorded.
[0128] Table 1
[0129]
[0130] It can be seen from the data in Table 1 above that the grouting material in the embodiment of the present invention is compared with comparative examples 1 to 5. When the expansion reaches the standard range of 180mm to 200mm, the setting time and compressive strength of the embodiment are faster and the compressive strength is higher than that of the comparative example. This means that the grouting material prepared by using industrial solid waste red mud in the present invention has more excellent strength performance and underwater performance. Similarly, by comparing Example 1 with Comparative Example 6, it is not difficult to see that the specific alkaline activator used in the embodiment of the present invention can effectively activate the performance of red mud and has excellent underwater setting time and strength; by comparing Example 1 with Comparative Example 7, it is not difficult to see that the specific anti-dispersion agent used in the embodiment of the present invention has more excellent underwater anti-dispersion performance.
[0131] Although the present invention has been illustrated and described with specific embodiments, it should be appreciated that the above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Those skilled in the art should understand that the technical solutions described in the above embodiments may be modified, or some or all of the technical features thereof may be replaced by equivalents without departing from the spirit and scope of the present invention. However, these modifications or replacements do not make the essence of the corresponding technical solutions deviate from the scope of the technical solutions of the embodiments of the present invention. Therefore, this means that all such replacements and modifications within the scope of the present invention are included in the appended claims.
Claims
1. An underwater non-dispersible grouting material, characterized in that: It includes the following components by mass: 150-250 parts of red mud, 10-80 parts of Portland cement, 1-8 parts of alkali activator, 3.5-10 parts of anti-dispersion agent, 0.5-8 parts of water reducer and some water; The alkaline activator comprises the following components: biomass ash, tungstate, silicate, microsilica powder, arginine and inorganic base.
2. The underwater non-dispersible grouting material according to claim 1, characterized in that: The underwater non-dispersible grouting material further comprises: 0.1 to 50 parts by mass of fly ash or 0.1 to 50 parts by mass of sulphoaluminate cement or both.
3. The underwater non-dispersible grouting material according to claim 1, characterized in that: The biomass ash includes at least one of corn cob ash, corn stalk ash or olive biomass ash; Preferably, the fineness modulus of the biomass ash is 200 mesh to 400 mesh.
4. The underwater non-dispersible grouting material according to claim 1, characterized in that: The tungstate includes at least one of sodium tungstate or potassium tungstate; and / or, the silicate comprises at least one of sodium silicate or potassium silicate; And / or, the inorganic base includes at least one of sodium hydroxide, potassium hydroxide or calcium hydroxide.
5. The underwater non-dispersible grouting material according to claim 1, characterized in that: Calculated by mass, the weight ratio of the components of the alkaline activator includes: 30-80 parts of biomass ash, 8-20 parts of tungstate, 15-30 parts of silicate, 5-10 parts of microsilica powder, 0.5-6 parts of arginine and 2-10 parts of inorganic base.
6. The underwater non-dispersible grouting material according to claim 1, characterized in that: The anti-dispersion agent includes polyvinyl alcohol modified with sodium alginate, cellulose compounds, stone powder and maltodextrin; Preferably, the weight ratio of the components of the anti-dispersant includes, by mass, 35-70 parts of polyvinyl alcohol modified with sodium alginate, 5-15 parts of cellulose compounds, 5-20 parts of stone powder and 4-8 parts of maltodextrin.
7. The underwater non-dispersible grouting material according to claim 1, characterized in that: The preparation method of the sodium alginate-modified polyvinyl alcohol comprises the following steps: A sodium alginate aqueous solution and a polyvinyl alcohol aqueous solution are prepared separately, and then the two are mixed, and an aqueous solution of a cross-linking agent is added dropwise thereto to react; After the reaction is completed, freeze drying is performed to obtain the sodium alginate-modified polyvinyl alcohol.
8. The underwater non-dispersible grouting material according to claim 1, characterized in that: The cross-linking agent includes at least one of calcium chloride, calcium sulfate, glutaraldehyde, and N,N'-methylenebisacrylamide; And / or, the mass ratio of the sodium alginate, the polyvinyl alcohol and the cross-linking agent is (0.9-3): (0.3-1.2): (1-5).
9. The method for preparing an underwater non-dispersible grouting material according to any one of claims 1 to 8, characterized in that: The steps include: The biomass ash, tungstate, silicate, microsilica powder, arginine and inorganic base are fully mixed to obtain an alkali activator; The red mud, the alkali activator and water are fully mixed, and then allowed to stand to obtain a mixture; The mixture, silicate cement, anti-dispersant and water reducing agent are fully mixed to obtain the underwater non-dispersible grouting material; Preferably, the standing time is 20 min to 40 min.
10. Use of the underwater non-dispersible grouting material according to any one of claims 1 to 8 in the field of construction engineering.
Citation Information
Cited By
Rigorous-environment-resistant underwater non-dispersible cement-based material
CN121225958A